The evolving global economy - Ohmae, Kenichi (A Harvard Business Review Book, 1985)
Although the semblance of a global economy has been with us for some time, Ohmae (The Borderless World) claims here that a "genuinely global economy really is something new under the sun. It observes laws and follows a logic all its own." This collection of 16 articles from the Harvard Business Review by a mix of business leaders, academics and journalists offers corporate managers strategies for dealing with it. Ohmae's "Putting Global Logic First" explores what he terms the demise of the nation-state and the shift to emerging economic region-states. Michael E. Porter ("Capital Disadvantage"), commenting on the decline of U.S. competitiveness, declares, "The U.S. system first and foremost advances the goals of shareholders interested in near-term appreciation of their shares-even at the expense of the long-term performance of American companies." Other articles describe the global economy from the perspectives of Europe, China, Singapore, Japan and Korea. This collection offers a high-level tour of global economic issues for informed readers